Factors associated with and kinetics of anti–IFN-α autoantibodies in RAG1/2 deficiency - Chen Wang, MD; David Evan Potts, MSc; Bijun Sun, MD; Marta Toth, PhD; Boglarka Ujhazi, MSc; Svetlana Sharapova, PhD; Rahim Miller, BS; Lindsey Rosen, PhD; Melis Yilmaz, BS; Kellie Larsen, MSc; Ottavia M. Delmonte, MD, PhD; Laura E. Poskitt, DO; et al. (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Autoantibodies against IFN-α (anti–IFN-α) have been reported in recombinase activating gene (RAG) deficiency, attributed to impaired central and peripheral T-cell/B-cell tolerance. However, the clinical features, especially viral infections, associated with these autoantibodies at baseline, their kinetics over time, and their response to hematopoietic cell transplantation are not well defined. Objective: We described the clinical and immunologic findings linked to anti–IFN-α IgG in RAG deficiency and tracked its kinetics longitudinally, including in those who underwent hematopoietic cell transplantation. Methods: We measured anti–IFN-α IgG by enzyme-linked immunosorbent assay in 80 RAG-deficient patients with curated clinical and immunologic data from a multinational collaboration. Results: Forty-eight patients (60.0%) had positive anti–IFN-α at baseline; these patients were typically older at time of testing, fulfilled the phenotype of delayed-onset combined immunodeficiency with granuloma and/or autoimmunity (70.8% vs 31.3%, P = .001), and had a history of more frequent viral infections, mainly from the Herpesviridae family (62.5% vs 21.9%, P < .001). These patients also showed higher levels of serum immunoglobulins and expanded populations of peripheral blood autoreactive-prone (CD19hiCD21lo) (14.3 vs 5.2%, P = .016) and double-negative (IgD−CD27−) B cells (12.8 vs 5.8%, P = .001). In cases with longitudinal evaluation, anti–IFN-α titers were largely stable, although an increase was observed with concurrent active cytomegalovirus infections. Despite some decline after transplantation, these autoantibodies persisted during follow-up. Conclusions: Anti–IFN-α autoantibodies reflect immune dysregulation in partial RAG deficiency. Their production is likely aggravated by environmental factors, especially frequent viral infections. Further studies are needed to define their pathogenic role in RAG deficiency.